Remarriage in The 'Iddah Perspective of Maqāṣid Al-Usrah: Study in Wedoro Waru, Sidoarjo, Indonesia - Sholihuddin, Muh.; Jazil, Saiful; Ni'am, Syamsun (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
Marriage is a multidimensional event, not only containing legal dimensions, but also a religious, cultural, social and even political event. Marriage is legal because it is regulated by law, as is worship because someone will receive a reward, then it contains cultural aspects because the marriage process is carried out according to custom. This study aims to reveal the role of kyai in the tradition of remarriage during the 'iddah period in Wedoro Waru, Sidoarjo Regency, East Java. The tradition of remarriage during the 'iddah period is a tradition that has been passed down from generation to generation. That article uses an empirical legal method explained by the theory of maqāṣid al- syarī'ah, data collection techniques namely interviews and documentation studies. This study found that remarriage during the 'iddah period carried out by kyai includes al-maṣlaḥah al-taḥsīniyyah, namely doing something good according to tradition and avoiding bad behavior that is reprehensible according to correct reason, so that life becomes safe, peaceful and looks beautiful in the eyes of people. other. Remarriage during the 'iddah period is a form of al-tajammul (beautiful) and al-iḥtiyāt (prudence). From the perspective of maqāṣid al-usrah, remarriage is a form of maintaining family welfare and realizing maqāṣid al-sharī'ah. This remarriage process is carried out by a kyai for both partners, because the kyai is considered to know the most about religious knowledge. Likewise, it can be emphasized that the marriage integration of the couple carried out by the Kiyai is a form of obedience to Islamic law as a form of prudence and creates maqāṣid al-sharī'ah.